2022
DOI: 10.1155/2022/9309327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lycopene Attenuating Injuries in Ischemia and Reperfusion

Abstract: Tissue and organ ischemia can lead to cell trauma, tissue necrosis, irreversible damage, and death. While intended to reverse ischemia, reperfusion can further aggravate an ischemic injury (ischemia-reperfusion injury, I/R injury) through a range of pathologic processes. An I/R injury to one organ can also harm other organs, leading to systemic multiorgan failure. A type of carotenoid, lycopene, has been shown to treat and prevent many diseases (e.g., rheumatoid arthritis, cancer, diabetes, osteoporosis, male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 244 publications
0
1
0
Order By: Relevance
“…Studies by Zhao et al 509 and Li et al 510 reported the beneficial effects of TCM components such as Astragalus, 511 , 512 Salvia Miltiorrhiza, 513 , 514 Angelica Sinensis, 515 , 516 Harpagide, 517 Icariin, 518 pachymic acid. 519 Zhao et al 509 and Li et al 510 have shown that treatment with Astragalus, 511 , 512 Salvia Miltiorrhiza, 513 , 514 Angelica Sinensis, 515 , 516 Harpagide, 517 Icariin, 518 pachymic acid, 519 and Lycopene 197 , 520 , 521 confer therapeutic effects against I/R injury in the heart, brain, and other organs. Moreover, Zhao et al 509 reported that TCM like Tricin, 522 Platycodin D, 523 Baicalein, 524 Lupeol, 525 Paeoniflorin, 526 and Bauhinia Championii 527 could activate the PI3K/Akt signaling pathway and mitigate brain I/R injury.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Studies by Zhao et al 509 and Li et al 510 reported the beneficial effects of TCM components such as Astragalus, 511 , 512 Salvia Miltiorrhiza, 513 , 514 Angelica Sinensis, 515 , 516 Harpagide, 517 Icariin, 518 pachymic acid. 519 Zhao et al 509 and Li et al 510 have shown that treatment with Astragalus, 511 , 512 Salvia Miltiorrhiza, 513 , 514 Angelica Sinensis, 515 , 516 Harpagide, 517 Icariin, 518 pachymic acid, 519 and Lycopene 197 , 520 , 521 confer therapeutic effects against I/R injury in the heart, brain, and other organs. Moreover, Zhao et al 509 reported that TCM like Tricin, 522 Platycodin D, 523 Baicalein, 524 Lupeol, 525 Paeoniflorin, 526 and Bauhinia Championii 527 could activate the PI3K/Akt signaling pathway and mitigate brain I/R injury.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Lycopene is a lipophilic compound, so the presence of fat in food enhances its absorption [24]. Its absorption is hampered by dietary fiber and beta-carotene [25]. After absorption from food, it is mainly stored in the liver, prostate, and adrenals.…”
Section: Lycopenementioning
confidence: 99%
“…It is also present in lower concentrations, e.g., in the brain and skin [3,26]. The adipose tissue contains more lycopene than serum because it is a lipophilic compound [25]. The average serum concentration is 0.2-1.0 µmol/L [27].…”
Section: Lycopenementioning
confidence: 99%